The occurrence of harmful algal bloom species in the east coast of Sabah, Malaysia - Mohammad Noor, Normawaty; Anwar, Encik Weliyadi; Ong, Fang Sing (2012)
Harmful algal bloom (HAB) has been reported in the west coast of Sabah since 1976 and the occurrences have caused negative fficts to human health and loss to aquaculture industry' However, no HAB has been reported in the east coast of Sabah although the causative organism has been reported in this area. Therefore, in order to evaluate the status of HAB in the east coast of Sabah, samples were collected at several sampling sites during both South West monsoon and North East monsoon' physical and chemical parameters were also recorded. Results showed that the causative organism found in the west coast of Sabah was not present in the study area. However other potential HAB species such as Ceratium furca has been identified. Comparison between physicol and chemical parameters between the east and west coast of Sabah showed signifficant differences in nutrients concentration between the east and west coast of Sabah. The presence of potential HAB species indicates that the east coast of Sabah may experience HAB problem in the future if factors triggering the bloom are not well managed